Implementation Of The EOQ Method In The Application Of The Goods Product Distribution Process - Juni Sasmiharti; Erni Karyati (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
Inventory is a model that is commonly used to solve problems related to efforts to control raw materials and finished goods in a business activity. Information systems for managing inventory are recommended to use computer-based software development to translate the size and complexity of information management. Software development which includes the stages of system analysis, design, coding, and testing. The next stage is to translate into the selected software to use the PHP Programming Language and MySQL Database. The system analysis has been discussed by involving employees as a source of development information as well as literature studies through books and journals. Based on the infrastructure management developed in this study, the business process operates better thanks to a computerized management system. The system created also has a reporting system that makes accountability to the leadership simple, fast, and accurate.